2014
DOI: 10.15740/has/fsrj/5.2/148-153
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of chironji (Buchanania lanzan) nut and kernels

Abstract: Buchanania lanzan (Chironji), a member of family Anacardiaceaecontains a hard nut that on decortication yields kernel containing about 52 per cent oil and used as a substitute for olive and almond oil while the whole kernel is used in sweet-meals. Although, the chironji nuts and kernels have been used extensively but the printed literature on their physical and engineering properties is scarce. In the present study, attempt has been made to generate primary data on physical and engineering properties which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
5
15
0
Order By: Relevance
“…The nuts were dried under the shade for 1 hr after the soaking and then subjected to sand roasting pre-treatment (Chadha, 2001;Sachan, Chauhan, Suresh, Singh, & Verma, 1993 Tables 2 and 3. The study showed that the chironji nuts had average geometric mean diameter of 8.74 ± 0.02, which is at par with studies conducted by Kumar, Prabhakar, Srivastav, and Bhowmick (2014), Kumar et al (2016), and Deshmukh, Dange, Pardeshi, and Borkar (2017). The sphericity of nut varied between 78.16 and 88.98% whereas kernel had average sphericity of 70.96%.…”
Section: Experimental Design and Proceduressupporting
confidence: 52%
“…The nuts were dried under the shade for 1 hr after the soaking and then subjected to sand roasting pre-treatment (Chadha, 2001;Sachan, Chauhan, Suresh, Singh, & Verma, 1993 Tables 2 and 3. The study showed that the chironji nuts had average geometric mean diameter of 8.74 ± 0.02, which is at par with studies conducted by Kumar, Prabhakar, Srivastav, and Bhowmick (2014), Kumar et al (2016), and Deshmukh, Dange, Pardeshi, and Borkar (2017). The sphericity of nut varied between 78.16 and 88.98% whereas kernel had average sphericity of 70.96%.…”
Section: Experimental Design and Proceduressupporting
confidence: 52%
“…When moisture content increases the moisture surrounds the surface of the seeds making them sticker. These seeds then aggregate together, thereby, increasing the angle of repose (Kumar et al, , ; Singh & Sahay, ). The relationship of angle of repose (degree) with moisture content is expressed in Equation (20). θ=0.4118MC+22.8340.25em()R2=.9878 …”
Section: Resultsmentioning
confidence: 99%
“…The true density is expressed as kg/m 3 . Porosity is measured as the void spaces present inside the seeds these are not occupied by the seeds (Kumar, Prabhakar, Srivastav, & Bhowmick, ). It is expressed in fraction or percentage.…”
Section: Methodsmentioning
confidence: 99%
“…The significance of the engineering properties of food processing is that they can be used in designing and simulation of food processes and equipment. The properties in which changes occur at different moisture levels are continuously required either at the starting off process or at any intermediate time (Kumar, Prabhakar, Srivastav, & Bhowmick, 2014;Rahman, 2009). The angle of repose and coefficient of friction has a critical role in crafting the hopper, silos, and conveyor belt for transportation, equipment to load and unload grains, packaging, and dehulling (Malik & Saini, 2016).…”
mentioning
confidence: 99%